Exercise training‐induced improvement in skeletal muscle PGC‐1α‐mediated fat metabolism is independent of dietary glycemic index. Issue 4 (April 2017) - Mulya, Anny; Haus, Jacob M.; Solomon, Thomas P.J.; Kelly, Karen R.; Malin, Steven K.; Rocco, Michael; Barkoukis, Hope; Kirwan, John P.
Abstract : Objective: This study hypothesized that a low‐glycemic diet combined with exercise would increase expression of nuclear regulators of fat transport and oxidation in insulin‐resistant skeletal muscle. Method: Nineteen subjects (64 ± 1 y; 34 ± 1 kg/m 2 ) were randomized to receive isocaloric high‐glycemic‐index (HiGIX; 80 ± 0.6 units, n  = 10) or low‐glycemic‐index (LoGIX; 40 ± 0.3 units, n  = 9) diets combined with supervised exercise (1 h/d, 5 d/wk at ∼85% HRmax ) for 12 weeks. Insulin sensitivity was determined by hyperinsulinemic‐euglycemic clamp. Skeletal muscle biopsies were obtained before and after the intervention to assess fasting gene and protein expression. Results: Weight loss was similar for both groups (9.5 ± 1.3 kg). Likewise, improvements in insulin sensitivity ( P  < 0.002) and PPARγ ( P  < 0.002), PGC‐1α ( P  = 0.003), CD36 ( P  = 0.003), FABP3 (mRNA, P  = 0.01 and protein, P  = 0.02), and CPT1B (mRNA, P  = 0.03 and protein, P  = 0.008) expression were similar for both interventions. Increased insulin sensitivity correlated with increased PGC‐1α expression ( P  = 0.04), and increased fasting fat oxidation correlated with increased FABP3 ( P  = 0.04) and CPT1B ( P  = 0.05) expression. Conclusions: An exercise/diet program resulting in 8% to 10% weight loss improved insulin sensitivity and key molecular mechanisms in skeletal muscle that are controlled by PGC‐1α. These effects were independent of the glycemic index of the diets.